Dare voce ai vissuti dei minori con diagnosi come intervento psicoanalitico - Fusacchia, Marta; Naruli, Maurizio; Schiopetti, Irene; Larcinese, Nadia; Nazzicone, Silvia (Quaderni di Psicologia Clinica, 2024)
The article aims to verify the possibility of proposing a desire within the psychoanalytic intervention with underage who have received a diagnosis. In particular, the problems that some services dedicated to underage encounter in relation to their diagnosed users will be discussed, trying to explore them from the perspective of the emotional experiences that characterize and organize them culturally.Services for underage are activated without their request; they are often activated on the request of the adults involved, or the institutions. This aspect has a profound value in clinical psychological intervention based on the analysis of the demand.Three collusive structures are proposed that influence the way in which interventions are culturally organized in these contexts: the diagnostic culture, the "underage" as a psychosocial position and the dimension of obligation that characterizes the culture of inclusion in the Italian school system. We aim to explore these collusive structures and the possible products that clinical psychological intervention can pursue in these contexts through three clinical experience reports that see a support teacher, an Educational Operator for Autonomy and Communication (OEPAC) and an educator from the Service for the Support of Minors in the Family (SISMIF) as professionals working with underage.
Keywords: school; diagnosis; childhood; Oepac; sismif